A Qualitative Study on the Implementation of Prevention and Identification Programs for Acute Respiratory Infections in Depok City, West Java - Bahasoan, Balqis Hiri; Hayati, Nisrina; Hamid, Endah Nurhalimah; Nurcandra, Fajaria (Universitas Tribhuwana Tunggadewi, 2024)
Acute Respiratory Infections (ARI) are among the most frequently reported infectious diseases in healthcare facilities. The ARI Prevention and Control Program aims to reduce ARI prevalence. This study seeks to provide in-depth understanding of the program's implementation at the Cinere Community Health Center, Depok. Using descriptive qualitative approach and rapid assessment test design, data collection occurred through in-depth interviews from April to June 2024. Four participants were selected using purposive sampling: ARI program managers from the Cinere Community Health Center and the Depok City Health Office, along with a teacher and a student from SMAN 9 Depok. The study focused on describing the program, its inputs, and its outputs. Data analysis was conducted using source triangulation.The results indicated that the ARI prevention program primarily focuses on promotive and preventive measures, with collaboration between the Health Office, the Community Health Center, and the community, particularly SMAN 9 Depok. While these activities are conducted regularly, strategies are required to enhance the program's effectiveness. This study concluded that the Cinere Community Health Center’s ARI prevention program has been well-executed, as it has engaged various community groups in promotive, preventive, rehabilitative, and curative efforts, alongside thorough recording and reporting. Nevertheless, further efforts are necessary to increase community participation, strengthen cross-sector collaboration beyond network clinics, expand outreach via digital media, and optimize the health information system for more efficient recording and reporting, ensuring the program's overall success.